1985
DOI: 10.1093/infdis/151.3.444
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Respiratory Virus Antigens in Middle Ear Fluids of Children with Acute Otitis Media

Abstract: Antigens of respiratory viruses were tested by immunoassay of the middle ear fluids and nasopharyngeal secretions of 137 children with acute otitis media. The following were found: (1) an epidemic of infection with respiratory syncytial virus (RSV) caused a significant increase in the occurrence of acute otitis media. (2) Fifteen percent of the children had RSV antigens in middle ear fluid, and in 7% RSV was the sole pathogen found. Adenovirus antigens were found in the middle ear fluid of 3% of the children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
3

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 14 publications
3
27
0
3
Order By: Relevance
“…In one study, RSV antigens were found in the middle ear fluid of 15% of children with AOM, and in 7% RSV was the sole pathogen found. 16 Studies in both hospitalized patients 17 and in a day-care setting 18 have suggested that the incidence of AOM is higher in RSV infection than it is in infection with other respiratory viruses (especially parainfluenza 1 through 3 and rhinovirus). Our outpatient data do not reveal striking relative differences among viruses in viral-associated AOM.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, RSV antigens were found in the middle ear fluid of 15% of children with AOM, and in 7% RSV was the sole pathogen found. 16 Studies in both hospitalized patients 17 and in a day-care setting 18 have suggested that the incidence of AOM is higher in RSV infection than it is in infection with other respiratory viruses (especially parainfluenza 1 through 3 and rhinovirus). Our outpatient data do not reveal striking relative differences among viruses in viral-associated AOM.…”
Section: Discussionmentioning
confidence: 99%
“…Paramyxoviruses, which include Sendai virus, Newcastle disease virus (NDV), respiratory syncytial virus, measles virus, and mumps virus, cause disease in many species (10,29,46,55,65). Nipah virus (NiV) is a highly pathogenic zoonotic paramyxovirus and emerging pathogen of this family.…”
mentioning
confidence: 99%
“…Editing in NiV produces a V protein and a W protein from the P gene (3,12,24,50,57). NiV V and W proteins have been shown to interact with signal transducer and activator of transcription 1 (STAT1) through the N-terminal domain shared with P, sequestering STATs in high-molecular-weight complexes (16,54,55). While NiV W and V proteins share identical N termini, the unique C terminus of NiV W contains a nuclear localization signal that compartmentalizes the effects of its interferon antagonism (56).…”
mentioning
confidence: 99%
“…44,45 Among the various mechanisms by which UAI may predispose patients to RAOM and COME, are inflammation and harm to the mucocilliary movement of the epithelium that lines the auditive tube, which has been experimentally 46 and clinically demonstrated. 47 …”
Section: Upper Airway Infectionsmentioning
confidence: 99%